2020
DOI: 10.3390/ijerph17249372
|View full text |Cite
|
Sign up to set email alerts
|

Religious Attendance in a Secular Country Protects Adolescents from Health-Risk Behavior Only in Combination with Participation in Church Activities

Abstract: Religiosity and spirituality have been considered to be protective factors of adolescent health-risk behavior (HRB). The aim of this study was to assess the relationship between adolescents’ HRB and their religiosity, taking into account their parents’ faith and their own participation in church activities. A nationally representative sample (n = 13377, 13.5 ± 1.7 years, 49.1% boys) of Czech adolescents participated in the 2018 Health Behavior in School-aged Children cross-sectional study. We measured religiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…This is why we may argue that not religion itself but only some religious communities, usually orthodox or with conservative interpretations of scripture, may share negative attitudes towards vaccination [ 18 , 51 , 63 ], as shown in our study conducted in a secular country where only a low percentage of religious people are predominantly Christian. Therefore, our results based on data from the secular environment of the Czech Republic are rather in line with studies, showing that spirituality without religious affiliation may lead to health-risk behavior [ 52 , 64 ], supporting this idea even in the field of vaccination.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is why we may argue that not religion itself but only some religious communities, usually orthodox or with conservative interpretations of scripture, may share negative attitudes towards vaccination [ 18 , 51 , 63 ], as shown in our study conducted in a secular country where only a low percentage of religious people are predominantly Christian. Therefore, our results based on data from the secular environment of the Czech Republic are rather in line with studies, showing that spirituality without religious affiliation may lead to health-risk behavior [ 52 , 64 ], supporting this idea even in the field of vaccination.…”
Section: Discussionsupporting
confidence: 89%
“…We assessed the following combinations of religious affiliation and spirituality: spiritual and religiously affiliated (S+RA; n = 55), spiritual but non-religiously affiliated (S+NRA; n = 35), non-spiritual but religiously affiliated (NS+RA; n = 72), non-spiritual and non-religiously affiliated (NS+NRA; n = 290). The number of respondents in each category is in line with the study of religiosity in the Czech Republic based on a representative sample [ 45 ] and other studies on R/S [ 50 , 51 , 52 ]. These results suggest that although some people from the Czech population consider themselves believers, they seeks spiritual fulfilment outside traditional religious institutions.…”
Section: Resultsmentioning
confidence: 70%
“…Therefore, our findings are consistent with the mainstream of the literature on the topic. [1][2][3][4][5][6][7][8][9][10][11][12] Despite the finding that only the Catholic religion was associated with a statistically significant IRR under 1, other religions (Muslim, Lutheran, and Orthodox) present an IRR lower than that of the Catholic religion. It could be suggestive of a difference between religions in the inhibitory power against smoking as it is found in Hussein et al 17 However, the failure of Wald tests to show the significance of that difference might be due to low number of non-Catholics in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between religious beliefs and risk taking behaviours has been found significant in young people. 1,2,3,4 Religious communities make up social networks that act as role models, provide social and emotional support, and promote the use of free time engaging in safe activities. 4 Religious practices influence actions and attitudes of persons, including those of adolescents, thereby facilitating the transmission of usually healthy lifestyles 5,6 , that following WHO foundational document must enable "a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity."…”
Section: Introductionmentioning
confidence: 99%
“…Nasim et al [32] reported that religion has a dissuasive effect on the risk behaviors of adolescents, interfering with their use of drugs by helping them to internalize messages that discourage consumption. The significant protective effect of religiosity in cannabis smoking has been reported in samples from diverse cultures [4,5,7,8,10,11,15,16,20,21,24,25,29,[31][32][33].…”
Section: Introductionmentioning
confidence: 91%